2020
DOI: 10.35848/1347-4065/abad17
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic properties and impedance analysis of (Li,Na,K)NbO3-based multilayered piezoceramics

Abstract: (Li,Na,K)NbO3-based multilayered piezoceramics were characterized by performing unipolar polarization electric field measurements and impedance spectroscopy. Subjecting an as-poled sample to up to 107 cycles in an applied 4 kV mm−1 unipolar cyclic field at 100 °C reduced its polarization by 8.9%. The impedance spectra of as-sintered, as-poled, and fatigued samples were acquired and analyzed. Two relaxation processes reported to occur in single-layered (Na,K)NbO3-based ceramics were identified. They occurred at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
3
2
0
Order By: Relevance
“…The activation energy for the bulk response increased from 0.87 ± 0.06 eV to approximately 1.12 ± 0.03 eV, with the most significant change occurring at 5 vol%. As previous studies suggested, the predominant conductive process in NKN is through oxygen vacancy migration at temperatures above 400 • C, with an activation energy between 0.98 and 1.41 [20,55,56]. The findings of the current study correspond well with these values.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The activation energy for the bulk response increased from 0.87 ± 0.06 eV to approximately 1.12 ± 0.03 eV, with the most significant change occurring at 5 vol%. As previous studies suggested, the predominant conductive process in NKN is through oxygen vacancy migration at temperatures above 400 • C, with an activation energy between 0.98 and 1.41 [20,55,56]. The findings of the current study correspond well with these values.…”
Section: Discussionsupporting
confidence: 90%
“…At 0 vol%, the activation energies for the bulk and grain boundary are 0.87 ± 0.06 eV and 1.26 ± 0.09 eV, respectively. Similar values have been calculated for similar materials and have been linked to the motion of ionized oxygen vacancies [20,40,52]. It should be noted that in oxide ceramics, background impurities are present, leading to intrinsic defects that contribute to the overall concentration of oxygen vacancies [40,53].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…10,[13][14][15][16][17][18][19][20][21][22] To establish an MBP similar to the PZT system, various lead-free solid solution systems have been investigated and composition-driven variations of crystal structure and properties have been studied. Since the discovery of (K, Na)NbO 3 -based ceramics with properties comparable to PZT, 23) (K, Na)NbO 3 [24][25][26][27][28][29][30] and its related Nb-based materials [31][32][33][34][35][36] have intensively studied with the aim of developing lead-free piezoelectric devices.…”
Section: Introductionmentioning
confidence: 99%